Non-linear analysis of reinforced concrete plates by the boundary element method and continuum damage mechanics - Fernandes, Gabriela Rezende; Araujo, Daniele [UNESP]; de Cerqueira Pituba, Jose Julio (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2009)
In this work, non-linear analyses of reinforced concrete plates are performed by using a BEM formulation, based on Kirchhoff's theory, which has already proved to be a robust technique to deal with plate problems. The non-linear behavior of concrete is modeled by the Mazars model, which is based on continuum damage mechanics (CDM) and has an easy parametric identification, while the reinforcement is governed by the uniaxial elasto-plastic model with constant hardening. Initially, the different types of damage models and their parametric identification are discussed and the Mazars model is presented. Then the BEM formulation is discussed, which is based on the initial moment technique, where the remaining domain integrals are evaluated by approaching the initial moment field over internal cells. The stress distribution over the plate thickness is obtained by using a Gauss scheme in which the adopted criterion is verified in each Gauss point defined along the plate. Then, the internal values of moments are approached by numerical integrals along the plate thickness. Finally, some numerical examples of reinforced concrete plates are analyzed, where the potentiality of the Mazars model is verified despite the difficulties of the parametric identification.
Keywords: boundary elements; damage mechanics; plate bending